An introduction to implicit bias : knowledge, justice, and the social mind - Beeghly, Erin; Madva, Alex (New York, NY : Routledge, 2020)
Written by a diverse range of scholars, this accessible introductory volume asks: What is implicit bias? How does implicit bias compromise our knowledge of others and social reality? How does implicit bias affect us, as individuals and participants in larger social and political institutions, and what can we do to combat biases? An interdisciplinary enterprise, the volume brings together the philosophical perspective of the humanities with the perspective of the social sciences to develop rich lines of inquiry. Itstwelve chapters are written in a non-technical style, using relatable examples that help readers understand what implicit bias is, its significance, and the controversies surrounding it. Each chapter includes discussion questions and additional annotated reading suggestions, and a companion webpage contains teaching resources. The volume is an invaluable resource for students--and researchers--seeking to understand criticisms surrounding implicit bias, as well as how one might answer them by adopting a more nuanced understanding of bias and its role in maintaining social injustice.
9. Epistemic Responsibility and Implicit Bias -- 10. The Specter of Normative Conflict: Does Fairness Require Inaccuracy? -- 11. Explaining Injustice: Structural Analysis, Bias, and Individuals -- 12. Individual and Structural Interventions -- Glossary -- Index
"Written by a diverse range of scholars, this accessible introductory volume asks: What is implicit bias? How does implicit bias compromise our knowledge of others and social reality? How does implicit bias affect us, as individuals and participants in larger social and political institutions, and what can we do to combat biases? An interdisciplinary enterprise, the volume brings together the philosophical perspective of the humanities with the perspective of the social sciences to develop rich lines of inquiry. Its 12 chapters are written in a non-technical style, using relatable examples that help readers understand what implicit bias is, its significance, and the controversies surrounding it. Each chapter includes discussion questions and additional annotated reading suggestions. And a companion webpage contains teaching resources. The volume is invaluable resource for students-and researchers-seeking to understand criticisms surrounding implicit bias, as well as how one might answer them by adopting a more nuanced understanding of bias and its role in maintaining social injustice"-- Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Prejudices; Discrimination; PHILOSOPHY / General